Meaningful Tourism in Asia - Gaurav Bhan Bhatnagar; Damba Gansukh; Deepti Gautam; Rameswar Khadka; Raveesh Mrigendra; Lajwanti Naidu; Wolfgang Georg Arlt (Language Assistance, 2025)
This article examines the applicability and transformative potential of the Meaningful Tourism paradigm as a strategic framework for sustainable tourism development in Asia, focusing on Mongolia, India (North and Northeast), and Nepal. Adopting a qualitative multi-case study approach, the research is based on document analysis, policy reviews, secondary statistical data, and comparative interpretation of international project reports and national tourism strategies. The analysis is anchored in the Meaningful Tourism framework, which evaluates tourism outcomes across six stakeholder groups: visitors, host communities, employees, tourism businesses, governments, and the environment through the lenses of shared value creation and stakeholder satisfaction. The findings reveal that Meaningful Tourism offers both a philosophical foundation and a practical governance tool to address key Asian tourism challenges, including overtourism, unequal benefit distribution, cultural commodification, and environmental vulnerability. Case evidence from nomadic tourism in Mongolia, artisan-led and community-based tourism in India, and diversified cultural and nature-based tourism in Nepal demonstrates the framework’s capacity to align policy, markets, and local livelihoods. While limited by its reliance on qualitative secondary data, the study contributes conceptually by advancing Meaningful Tourism as an integrative, context-sensitive pathway for resilient and inclusive tourism futures, calling for future empirical research to operationalise indicators and measure long-term impacts